In vitro toxicological evaluation of mesoporous silica microparticles functionalised with carvacrol and thymol. (February 2022) - Fuentes, Cristina; Fuentes, Ana; Byrne, Hugh J.; Barat, José Manuel; Ruiz, María José
Abstract: The cytotoxicity of carvacrol- and thymol-functionalised mesoporous silica microparticles (MCM-41) was assessed in the human hepatocarcinoma cell line (HepG2). Cell viability, lactate dehydrogenase (LDH) activity, reactive oxygen species (ROS) production, mitochondrial membrane potential (ΔΨm), lipid peroxidation (LPO) and apoptosis/necrosis analyses were used as endpoints. The results showed that both materials induced cytotoxicity in a time- and concentration-dependent manner, and were more cytotoxic than free essential oil components and bare MCM-41. This effect was caused by cell-particle interactions and not by degradation products released to the culture media, as demonstrated in the extract dilution assays. LDH release was a less sensitive endpoint than the MTT (thiazolyl blue tetrazolium bromide) assay, which suggests the impairment of the mitochondrial function as the primary cytotoxic mechanism. In vitro tests on specialised cell functions showed that exposure to sublethal concentrations of these materials did not induce ROS formation during 2 h of exposure, but produced LPO and ΔΨm alterations in a concentration-dependent manner when cells were exposed for 24 h. The obtained results generally support the hypothesis that the carvacrol- and thymol-functionalised MCM-41 microparticles induced toxicity in HepG2 cells by an oxidative stress-related mechanism that resulted in apoptosis through the mitochondrial pathway. Highlights: Functionalised MCM-41 was more cytotoxic than carvacrol, thymol and bare particles. Both functionalised particles behaved similarly as regards their cytotoxic effects. Cytotoxicity was caused by direct cell-particle interactions. Cytotoxicity was related to an oxidative stress mechanism that led to apoptosis.